Предмет:
МатематикаАвтор:
аноним1) а) f(x) = 1/5x5 - x3 + 4.
f\'(х) = 1/5 * 5 * х4 – 3х² = х4 – 3х².
б) f(x) = (3x – 1)/x3.
Производная произведения: (f * g)\' = f\' * g + f * g\'.
f\'(х) = (3x – 1)\' * x3 + (3x – 1) * (x3)\' = 3 * x3 + (3x – 1) * 3x² = 3x3 + 9x3 – 3x² = 12x3 – 3x².
в) f(x) = 1/(2cosx).
Производная дроби: (f/g)\' = (f\' * g - f * g\')/g^2.
f\'(х) = (1\' * 2cosx - 1* (2cosx)\')/( 2cosx)^2 = (0 - 1* (-2sinx))/2cos²x = sinx/cos²x.
2) а) f(x) = xsinx.
f\'(х) = х\' * sinx + х * (sinx)\' = sinx + хcosx.
x = П/2; f\'(П/2) = sinП/2 + П/2cosП/2 = 1 + П/2 * 0 = 1.
б) f(x) = (2x - 3)6.
f\'(х) = 6(2х – 3)5 * (2х – 3)\' = 6(2х – 3)5 * 2 = 12(2х – 3)5.
х = 1; f\'(1) = 12(2 * 1 – 3)5 = 12 * (-1)5 = -12.
3) а) f(x) = 2sinx – X.
f\'(х) = 2cosx – 1.
f\'(х) = 0; 2cosx – 1 = 0.
2cosx = 1.
cosx = ½.
х =±П/3 + 2Пn, n – целое число.
b) f(x) = x5 + 20x².
f\'(х) = 5х4 + 20х.
f\'(х) = 0; 5х4 + 20х = 0.
х(5х3 + 2) = 0.
Отсюда х = 0.
Или 5х3 + 2 = 0; 5х3 = -2; х3 = -2/5; х = 3√(-2/5).
Автор:
marshallmclaughlinДобавить свой ответ